SOCIAL SUPPORT AND SELF ESTEEM AS CORRELATES OF PSYCHOLOGICAL WELLBEING AMONG ADOLESCENTS IN ILORIN METROPOLIS - Ajao, Paul O.; Ajao, Tunmise S.; Oguntayo, Rotimi; Adeyi, Margaret A. (African Journal of Social and Behavioural Sciences, 2024)
Whilst the pursuit for wellbeing is virtually universal, the path to its attainment varies largely among individuals as a result of several factors. This present study adopted an Ex-post facto design to investigate psychological well-being among adolescents in Ilorin metropolis in relation to self-esteem and social support. Rosenberg Self-esteem Scale (RSES), Berlin Social Support Scale (BSSS) and World Health Organization-Five (WHO-5) were used to measure self-esteem, social support and psychological well-being respectively while 576 participants made of 375 males and 201 females between the ages of 14-22 years were conveniently sampled. The study's results indicated that self-esteem and social support, jointly influenced psychological wellbeing [F (2, 565) =33.914; p<.05]. Also, the analysis of the independent variable showed that self-esteem (t =-4.164; p<.05; β = -.200) and social support (t = 6.391; p<.01; β =.306) had an independent influence on psychological wellbeing. The second hypothesis revealed that participants with high self-esteem reported high level of psychological well-being than participants with low self-esteem. Likewise, third hypothesis revealed that female participants reported high level of psychological wellbeing than male participants. This study concluded that there is significant influence of self-esteem and social support on the psychological well-being of adolescents. The study recommends the importance of parents, educators, and psychologists to recognize the need to provide active social support to adolescents through healthy social relationships to cultivate a robust self-esteem in order to promote favourable psychological well-being.